Political economy of development finances from the emerging donors: the case of infrastructure projects in Bangladesh - Sikder, Nawsher (2024)
As the second-highest recipient of China's development finances in South Asia and the highest recipient of India's development finances globally, Bangladesh has emerged as a classical instance of a country entangled amid the power struggle for influence between China and India. This thesis seeks to understand how Bangladesh, a secondary power, responds to the rivalry between the two much larger and powerful neighbours vying for influence and how Bangladesh’s response to the China-India rivalry with the use of development finances has been shaped by the systemic factors of international politics and unit-level factors of domestic politics and economy. In addition, it also investigates how the response of Bangladesh in relations to the acceptance of development finances from China and India affects its domestic politics, infrastructural development and debt sustainability. The theoretical framework of the study derives insights from the concepts of neoclassical realism and hedging, which help define the formation and nature of the multiple strategies adopted by Bangladesh. The mediation between the systemic and unit-level variables explains the shaping of the perception of the leadership leading to the formation of the country's response to the rivalry between the two competing giants. Embracing thematic data analysis technique in line with the qualitative methodology, this study conducts forty-seven interviews of expert and elite respondents and examines the secondary data derived from official documents, journal articles, newspaper articles, and blogs. This research contributes to the understanding on how the development strategies and foreign policy responses of the recipient countries are influenced by the power struggle between the emerging donors such as China and India, offering insights into secondary states' navigating geopolitical complexities in the pursuit of economic growth and stability. The study also recommends the pathways for formulating and reorienting policies and strategies to make the response more effective and ensure better utilisation of the accepted development finances.